Bio-fortified Compost as A Substitute for Chemical N Fertilizer for Growth, N Accumulation, and Yield of Sweet Corn - Marwanto, Marwanto; Wati, Shinta Puspita; Romeida, Atra; Handajaningsih, Merakati; Adiprasetyo, Teguh; Hidayat, Hidayat; Purnomo, Bambang; Murcitro, Bambang Gonggo; Siswanto, Usman (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
ABSTRACTFinding the appropriate method of fertilizer application to simultaneously enhance farm productivity and ensure ecosystem sustainability has been receiving a lot of attention. A field experiment was carried in the Research Plot Agriculture Faculty Bengkulu University Campus Indonesia in 2017. The purpose of this study was (1) to assess the significant effects of inorganic N fertilizer (IF) substitution with bio-fortified compost (BC) under equal N conditions on growth, N accumulation, and yield of sweet corn, and (2) to determine the appropriate level to which inorganic N fertilizer could be reduced and equivalently replaced by bio-fortified compost to promote sweet corn growth and yield. The treatments consisted of six different proportions of inorganic N fertilizer (IF) substitution with bio-fortified compost (BC). Each treatment was designed on the basis of equal amount of total N input from a combination of both fertilizers (138 kg N ha-1). They were arranged in a randomized block design with 3 replications. They included (1) 100% IF plus 0% BC, (2) 75% IF plus 25% BC, (3) 50% IF plus 50% BC, (4) 25% IF plus 75%, (5) 0% IF plus 100% BC, and (6) no IF and no BC. The results showed that the increasing proportion of IF replaced by BC resulted in an increase for all variables (except for plant height) but they decreased when 100% IF substitution with 100% BC was applied. Among the partial substitution treatments, 50% IF plus 50% BC consistently produced the best growth, N accumulation, and yield increase. Treatments of 50% IF plus 50% BC and 25% IF plus 75% BC produced the highest green cob weight with husk per plot (10.74 – 10.84 kg plot-1), which was 16% to 19% higher than treatment of 100% IF plus % BC. The three partial substitution treatments produced crop yield components as good as treatment of 100% IF plus 0% BC. Treatment of 0% IF plus 100% BC reduced plant growth, N accumulation, and crop yield and its components. The appropriate level to which IF could be reduced and equivalently replaced by BC was at the range of 25% to 75%. Hence, a suitable replacement of inorganic N fertilizer with bio-fortified compost is considered a reasoned way to simultaneously increase crop yield and reduce environmental degradation.Keywords: organic fertilizer, chemical fertilizer, bio-fortification, chemical fertilizer substitution, bio-fortified compost